(untitled) (Confluenţe Bibliologice, 2019)
The Great Union of 1918 is the priceless good left to the descendants of the generation of the early twentieth century. The Great Union Centennial represents a moment of crossroads and a solemn occasion to renew the country project that brings us together, to rebuild solidarity between Romanians. The article is a retrospective of the events held in the Romanian Information Centre during 2018, the year of the Great Union Centennial.